A pragmatic analysis of manipulative speech acts used by American and Arabic attorneys in selected criminal trials - Dahaam, Ziyad Ahmed; Salih, Ahmed Mohammed (Edelweiss Applied Science and Technology, 2024)
The present study investigates the manipulative speech acts used by American and Arabic attorneys while defending their clients in criminal trials. It is hypothesized that they construct their arguments on the basis of such type of speech acts to mislead the members of the jury who expect to listen to concrete evidences of innocence. The study follows a qualitative analysis to achieve the aims in terms of the modal adopted. The model is applied to six selected arguments divided between American and Arabic attorneys. Each part is resembled by an attorney. The results show that they both use indirect speech acts of manipulation, with some notable differences. The conclusions are drawn on the basis of their manipulative speech acts and on the basis of the comparison between the two attorneys which prove that they resort to two different types of indirect speech acts to manipulate the members of the jury.